Answer: Use PEMDAS. 11^2 (11 times 11) = 121.
2^2 (2 times 2) = 4
121 x 4 = 484
Step-by-step explanation:
Using the Pemdas method, you can solve the equation.
Answer:
Step-by-step explanation:
w^3 + 4w^2 + 5w - 12
I WILL ANSWER SO TIMMY GET CROWN
Answer:
Fifth Day (1024 pounds)
Step-by-step explanation:
For every subsequent day, he collected 4 times the previous day.
This increase is a ratio/product, therefore the sequence is a geometric sequence.
The nth term of a geometric sequence,
Where:
a=first term
r=common ratio
n=number of terms
Corey collected 4 pounds of newspaper on day 1., a=4
After day one he collected 4 times the amount and for every subsequent day, he collected 4 times the previous day. r=4
We want to determine on which day he will first collect over a 1000 pounds of new paper.
In order to apply law of indices, we look for the next term greater than 250 which is an index of 4.
Therefore on the fifth day, he will collect an amount over 1000 pounds, precisely 1024 pounds.
Answer:
sqrt 5 = 2.23606798
Step-by-step explanation:
Thank you for telling us the 2 is squared that really helps!
x^2 - 5 = 0
(add 5 both sides)
x^2 = 5
(sqrt both sides) (sqrt stands for square root)
x = sqrt 5
(Usally they just want sqrt 5 as an answer but if they want decimals its)
x = 2.23606798
Answer:
x=
Step-by-step explanation:
f(x)=-5
-5=0
Add 5 to both sides.
=5
To get rid of the square of x, put the square root thingie so that it will cancel out. BTW, if you put it on one side, you have to put it on the other side.
=
x=
Hope this helps! Plz give brainliest!
The larger of two numbers is 1 more than twice the smaller. The sum of the numbers is 20 less than three times the larger. Find the numbers. I NEED help please. I'm getting extremely frustrated!!
Answer:
13 and 6
Step-by-step explanation:
Let x = larger number
Let y = smaller number
The larger of two numbers is: x =
one more than twice the smaller: 2y + 1
x = 2y + 1 {equation 1}
The sum of the numbers is: x + y =
20 less than three times the larger: 3x - 20
x + y = 3x - 20
This can be simplified. Subtract 3x from both sides.
x - 3x + y = -20
-2x + y = -20 {equation 2}
Since we already know from equation 1 that x=2y+1, substitute that into equation 2
and solve for y:
-2(2y+1) + y = -20
-4y - 2 + y = -20
-3y - 2 = -20
-3y = -18
y = -18/(-3)
y = 6
x = 2y+1 = 2(6)+1 = 12 + 1 = 13
Your numbers are 13 and 6